The ultimate Daily Show and philosophy : more moments of Zen, more indecision theory - Holt, Jason (Chichester, West Sussex : Wiley Blackwell, 2013)
Savor moments of Zen like never before, with our Senior Philosophical Correspondents The Ultimate Daily Show and Philosophy is revised, expanded, and updated to probe deeper than ever before the philosophical significance of the quintessential "fake" news show of the 21st century. Features significant revisions and updates from the first 2007 editionIncludes discussion of both The Daily Show and its spin-off, The Colbert Report. Reveals why and how The Daily Show is philosophically engaging and significant. Showcases philosophers at their best, discussing truth, knowledge, reality, and the American Way. Faces head on tough and surprisingly funny questions about politics, religion, and power.
Really? You're Jewish?Team Buber; Passover v. Easter; Earth (The Book)-Mocking the Sacred; The New Jersey Connection; Notes; Segment 3 Field Report: Politics and Critical Thinking; 10 More Bullshit: Political Spin and the PR-Ization of Media; The Essence of Bullshit and the Truth about Lies; Liars, Liars, Pants on Fire; More Bullshit, Piled Higher and Deeper; A New Spin on an Old Art; Was Frankfurt BS-ing about Spin?; PR-ization of the Media; Spin Alley; Truth Matters; Notes; 11 The Senior Black Correspondent: Saying What Needs to Be Said; Satire: A Tradition of Cultural Criticism.
Print version record.
Keywords: Daily show (Television program); Daily show (Television program); Daily show (Television program); PERFORMING ARTS -- Reference; Electronic books